Bestsellers: Popular Fiction Since 1900 - Bloom, Clive. author. aut Link
XXII, 459 p. 2 illus., 1 illus. in color.
Keywords: This book charts the publishing industry and bestselling fiction from 1900, featuring a comprehensive list of all bestselling fiction titles in the UK. This third edition includes a new introduction which features additional information on current trends in reading including the rise of Black, Asian and LGBTQIA+ publishing; the continuing importance of certain genres and up to date trends in publishing, bookselling, library borrowing and literacy. There are sections on writing for children, on the importance of audiobooks and book clubs, self- published bestsellers as well as many new entries to the present day including bestselling authors such as David Walliams, Peter James, George R R Martin and far less well known authors whose books s sell in their thousands. This is the essential guide to best-selling books, authors, genres, publishing and bookselling since 1900, providing a unique insight into more than a century of entertainment, and opening a window into the reading habits andsocial life of the British from the death of Queen Victoria to the Coronavirus Pandemic. .